Performance, Emission and Combustion of LPG Diesel Dual Fuel Engine Using Glow Plug - Nakkeeran, S. (International Journal of Psychosocial Rehabilitation, 2019)
A single-cylinder vertical air-cooled diesel engine was modified to use LPG in dual fuel mode to study the performance, emission, and combustion characteristics. The primary fuel, liquefied petroleum gas (LPG), was mixed with air, compressed, and ignited by a small pilot spray of diesel. The dual-fuel engine showed a reduction in oxides of nitrogen and smoke in the entire load range. However, it suffers from the problem of poor brake thermal efficiency and high hydrocarbon and carbon monoxide emissions, particularly at lower loads due to poor ignition. In order to improve the performance at lower loads, a glow plug was introduced inside the combustion chamber. The brake thermal efficiency improved by 3% in the glow plug assisted dual fuel mode, especially at low load, and also reduced the hydrocarbon, carbon monoxide, and smoke emissions by 69%, 50%, & 9%, respectively. The presence of a glow plug had no effect on oxides of nitrogen.